Perlunya Penguatan Peran dan Fungsi Komisi Yudisial dalam Membangun Peradilan yang Bersih dan Berwibawa. - Mahayoni Mahayoni (President University, 2015)
Law enforcement in Indonesia is still far from the expectations of all parties. The capture of the law enforcement agencies such as lawyers, prosecutors, judges, by the Corruption Eradication Commission or KPK is a fact which shows the weakness of the legal system in Indonesia that has not touched the sense of justice. This can also be an iceberg. That is indeed a violation or crime committed by law enforcement actually be much more that has not been revealed. But the efforts of various parties such as NGOs NGOs that fight for justice laws that could answer the sense of justice in society should be appreciated.Justice in the field of law is not come by itself but must be fought by all parties. The establishment of institutions that provide surveillance from the Police Commission, the Prosecutorial Commission and the Judicial Commission is something that should be appreciated. However, people are still waiting for this role to the maximum watchdog agency. The fact shows the role of supervisory institutions is only to observe, provide feedback, report to the media and has not appeared any decisive action monitoring results of the independent supervisory commission. This situation is more worrying seizure or tug their authority on the independent commission commission. In this study, the authors highlight the tug of the role of the Judicial Commission in charge of Justice. Candidate recruitment problems and forth between the judges into the judicial authority or the Judicial Commission. The authority was invited there any laws regarding the recruitment of judges sued by Indonesian Judge Association. This means that if the prospective judges are not recruited correctly from the beginning and just rely on the connection, kinship likely to judge who are the guardians of justice last very likely filled by people who have no competence. If this situation is allowed then people's expectations so that the law can touch the sense of justice for the community is still far and should be pursued.